A adoção do padrão internacional contábil e sua influência na estrutura de capital das empresas brasileiras: um quase-experimento - Tristão, Pâmela Amado (2019)
The capital structure of a company consists on the proportion of equity and thirty-part capital, which signs information related to its financing structure, making the company susceptible to the agents’ evolution which impacts on their expectations of lower or higher probability of investment returns. In this context, corporate governance arises as a mechanism to guarantee investor their rights regarding the capital invested. The Brazilian stock market has been showing evolution in terms of these practices, such us the adoption of the International Financial Reporting Standard (IFRS) established through Law 11.638 (2007), which allowed, through the implementation between 2007 and 2009, the issue of Brazilian reports following the international standard. Although this law affected the way a considerable number of publicly traded companies were used to issue their financial and accounting information, a group of companies was already adequate to it in the period before the law was enforced due to the dual listing by the issuance of American Depositary Receipts (ADRs). The objective of this study was to analyze the influence of corporate governance on the capital structure by comparing companies that adequate to international accounting standards in the period prior the law 11.638 (2007) and companies that adhered by the imposition. To achieve it, a quasi-experimental study was carried out using the Differences in Differences (DID) methodology, which allowed the comparison of leverage levels, both at market and book value, as well as net indebtedness of companies segmented in treatment (companies affected by the law) and control (ADRs issuing companies) in the period before and after the law. The graphical analysis evidenced the premise of parallel trends in leverage measures at market value, satisfying the initial premise of DID application. Subsequently, the model estimation has evidenced changes in the capital structure influenced by the strong effect of control group, whose leverage level increased. The DID coefficient was statistically significant for market measures, evidencing higher levels of indebtedness in companies issuing ADRs in the period after the law, compared to companies that adhered to the international standard by imposing it. The results also showed that, regarding a set of independent variables, the investment and growth opportunity, as well as the company’s size were identified as the capital structure most relevant variables, confirming the Trade-Off theory.